2015
DOI: 10.1111/jvs.12331
|View full text |Cite
|
Sign up to set email alerts
|

Edaphic filters and the functional structure of plant assemblages in grasslands in southern Brazil

Abstract: Questions We analysed trait convergence and trait divergence assembly patterns across a metacommunity of grassland types (dry, wet and rocky) occurring along an edaphic gradient. We asked whether (1) floristics and phylogenetic structures vary among grassland types; (2) there is convergence and/or divergence in plant traits along the gradient; (3) the functional structure is influenced by phylogeny; and (4) abiotic or biotic filters generate the assembly patterns. Location Campos Gerais region, Paraná State, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 54 publications
1
13
0
7
Order By: Relevance
“…Environmental filtering appears to be more important in Control than C‐additions whereas environmental and biotic filters may have contributed to a community's phylogenetic structure following C‐additions. Similarly, Maire et al () and Moraes et al () noted that a combination of environmental and biotic filters structured grassland communities. At the same time, there are two important caveats to consider.…”
Section: Discussionmentioning
confidence: 86%
“…Environmental filtering appears to be more important in Control than C‐additions whereas environmental and biotic filters may have contributed to a community's phylogenetic structure following C‐additions. Similarly, Maire et al () and Moraes et al () noted that a combination of environmental and biotic filters structured grassland communities. At the same time, there are two important caveats to consider.…”
Section: Discussionmentioning
confidence: 86%
“…Moraes et al. ). Additionally, it may be instructive to contrast the functional traits of generalists (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the growing support for the DEFH along elevational gradients, it is now important to test if the predictions of this model also hold across other gradients, or whether the ALH explains the distribution of alien species along, for example, aridity or salinity gradients (especially since environmental filtering plays a significant role along many edaphic gradients; e.g. Moraes et al 2015). Additionally, it may be instructive to contrast the functional traits of generalists (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Previous soil analyses showed that the soil chemicals and structural characteristics are similar among both areas, but the soils in VVL are considered to be richer than those in GUA because of their lower sandiness and higher concentration of K and Mn (Moraes et al . ). Whereas the physiognomy of the two studied sites are similar, the species composition is quite different (http://onlinelibrary.wiley.com/doi/10.1111/aec.12270/suppinfo).…”
Section: Methodsmentioning
confidence: 97%